Proteome Changes of Human Bone Marrow Mesenchymal Stem Cells Induced by 1,4-Benzoquinone - Wu, Wei (Biomed Res Int, 2016)
Benzene is metabolized to hydroquinone in liver and subsequently transported to bone marrow for further oxidization to 1,4-benzoquinone (1,4-BQ), which may be related to the leukemia and other blood disorders. In the present study, we investigated the proteome profiles of human primary bone marrow mesenchymal stem cells (hBM-MSCs) treated by 1,4-BQ. We identified 32 proteins that were differentially expressed. Two of them, HSP27 and Vimentin, were verified at both mRNA and protein levels and their cellular localization was examined by immunofluorescence. We also found increased mRNA level of RAP1GDS1, a critical factor of metabolism that has been identified as a fusion partner in various hematopoietic malignancies. Therefore, these differentially expressed proteins can play important roles in benzene-mediated hematoxicity.